KEBUGARAN JASMANI DAN ROHANI PERSPEKTIF TEOLOGI HINDU - Yunitha Asri Diantary Ni Made (Jnanasidanta, 2020)
Body fitness is one of the important things that need to be considered in life, sometimes humans forget to take care of the body which is the main key in the success or failure to do activities. The better physical fitness of a person, the stronger the physical or endurance they have. Caring for physical fitness is not only felt by the physical, various bodily functions and mental health will have a positive impact. Seeing the importance of the meaning of the physical body in the Hindu view, then in the Vedas and all the knowledge that becomes its branches always emphasize in its description, that the care of the physical body, both those related to cleanliness, health, purity and all related matters should be maintained with orderly, harmonious and remain conducive. Regular physical body care according to the principles of dharma, sistacra or sacred traditions is considered religious worship, soul which is a spark of Parama atma (Brahma) can reside comfortably in it. A clean and holy Physical Body will awaken the spiritual fitness of the human being. The method used in this study is a descriptive method that will systematically describe the physical fitness of the human body physically and spiritually.